OUTCOME OF MODIFIED OPEN SURGERY IN TENNIS ELBOW - Khan, Muhammad Shoaib; Kamran, Haider; Khan, Shamsher Ali; Ahmed, Mukhtar; Khan, Alamzeb; Younas, Mohammad; Khan, Sadulah (Journal of Ayub Medical College Abbottabad, 2007)
Background: Tennis elbow is a common disorder of upper extremity. It can be treated conservatively in majority of the patients but some resistant cases eventually need surgery. Material & Methods: This descriptive study was conducted at Department of Orthopaedics, Ayub Teaching Hospital, Abbottabad, from January 2002 to June 2006. Sixteen patients had surgical release of the extensor tendon origin along with excision of the lateral epicondyle ridge. These patients did not res pond to conservative treatment i.e. rest, non- steroidal anti inflammatory drugs (NSAIDS), local steroid injections and physiotherapy. Patients were followed upto six months. Outcome was graded as excellent, good and poor according to pain relief and function of the hand. Results: Sixteen patients (17 elbows) were studied. Thirteen were female (81.25%) and three were male (18.75%). Fifteen patients (93.75%) had unilateral Tennis Elbow, while one had bilateral involvement (6.25%). In unilateral disease, right side was affected in eleven patients (68.75%) and left side in four (25%). Excellent outcome was noticed in eleven patients (68.75%) and good result in five patient (31.25% ). Conclusion: Open surgical technique of releasing extensor tendon origin along with excision of lateral condylar ridge of the humerus is new and simple procedure and yields excellent and good result in patients with resistant Tennis Elbow Keywords: Tennis elbow, lateral, epicondylitis